ON THE STARK BROADENING OF Os II SPECTRAL LINES - Dimitrijević, Milan S. (Bulletin of Natural Sciences Research, 2020)
Stark broadening parameters, full widths at half maximum (FWHM) and shifts for 13 Os II lines have been calculated. The plasma parameters are: electron density of 1017 cm-3 and temperatures from 5 000 K to 80 000 K. Calculations have been performed with the simplified modified semiempirical (SMSE) approach. The results are also used for the consideration of Strak width and shift regularities within the Os II 6s6D-6p6Do multiplet.